2019
DOI: 10.1371/journal.pone.0216723
|View full text |Cite
|
Sign up to set email alerts
|

A metadata approach to evaluate the state of ocean knowledge: Strengths, limitations, and application to Mexico

Abstract: Climate change, mismanaged resource extraction, and pollution are reshaping global marine ecosystems with direct consequences on human societies. Sustainable ocean development requires knowledge and data across disciplines, scales and knowledge types. Although several disciplines are generating large amounts of data on marine socio-ecological systems, such information is often underutilized due to fragmentation across institutions or stakeholders, limited standardization across scale, time or disciplines, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Whilst meta-data is publically available for some of projects (e.g., Mascareñas-Osorio et al, 2017;Comunidad and Biodiversidad, 2018;Palacios-Abrantes et al, 2019) in public repositories, project data are not publically available in open access databases. The exception to this rule is Naturalista, where all information is immediately published online, can be consulted by anybody with internet access, and can be downloaded in full.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst meta-data is publically available for some of projects (e.g., Mascareñas-Osorio et al, 2017;Comunidad and Biodiversidad, 2018;Palacios-Abrantes et al, 2019) in public repositories, project data are not publically available in open access databases. The exception to this rule is Naturalista, where all information is immediately published online, can be consulted by anybody with internet access, and can be downloaded in full.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that strong asymmetry exists in scientific research and funding across the US–Mexico border. Seven times more scientific articles have been published on the US population than the Mexican population, despite the fact that the Baja Peninsula is a hotspot for marine research activity in Mexico (Palacios‐Abrantes et al., 2019). Among the three articles that contained data on Mexican GSB populations, none addressed the past or ongoing fishery, a trend seen for many other coastal fisheries in the California Current region (Erisman et al., 2010; Johnson et al., 2017; Sáenz‐Arroyo et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Metadata, data about data, is well known to be of significant importance (Damerow et al 2021) and can be mined for information (Palacios-Abrantes et al 2019). It is needed in the process of publishing the recorded data to for instance (GBIF 2020), OBIS (UNESCO 2020) and SeaDataNet (Pecci et al 2020, Schaap andLowry 2010).…”
Section: Introductionmentioning
confidence: 99%